2017
DOI: 10.30616/ajb.343665
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of resveratrol against zinc oxide induced nanotoxicity

Abstract: Zinc oxide (ZnO) is a compound that has harmful effects as well as being used in many different areas. Numerous studies have been carried out to minimize the toxic effects of ZnO nanoparticles (NPs). In the present study, the protective role of resveratrol (RSV), a potent antioxidant polyphenol substance, was examined against ZnO-induced nanotoxicity on human pulmonary alveolar epithelial cells (HPAEpiC). In this context, the cytotoxic and genotoxic effects of different concentrations of RSV (5, 10, 20 mg/L) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, stilbenoids from grape cane extracts might lower the potential nanotoxicity of zinc oxide, as recently proposed by Emsen and Turkez. 32 Further studies might focus on the interactions regarding the stability and fungicidal efficacy of such promising combinations.…”
Section: Impact Of Physical Uv Filtersmentioning
confidence: 99%
“…In addition, stilbenoids from grape cane extracts might lower the potential nanotoxicity of zinc oxide, as recently proposed by Emsen and Turkez. 32 Further studies might focus on the interactions regarding the stability and fungicidal efficacy of such promising combinations.…”
Section: Impact Of Physical Uv Filtersmentioning
confidence: 99%
“…It acts through signaling pathways related to growth factors and receptor tyrosine kinases and interferes with signal transduction by the growth factor β. Experimental studies have demonstrated that resveratrol might impact apoptosis by regulating molecules that comprise caspase-3, p53, peroxisome proliferatoractivated receptor, NfκB, Bax, Bcl-2, and apoptotic protease activating factor-1 (Emsen and Turkez, 2017;Rauf et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within phytochemicals, resveratrol, a compound occurring in many fruits like grapes, mulberries, peanuts, and cocoa, has been widely reported to exhibit antioxidant and scavenging activities [23]. In addition, emerging studies have reported a protective role of resveratrol against toxicity induced by nanomaterials [24] and ZnO NPs in epithelial cells, Nile tilapia, and Caenorhabditis elegans [25,26]. While there is a copious number of in vitro studies on the protective effects of antioxidants against NP-induced damage, there are few works carried out in vivo, and none in zebrafish embryos despite the advantages related to their utilization.…”
Section: Introductionmentioning
confidence: 99%